Antibacterial Screening of Bacterial Isolates Associated with Mangrove Soil from the Ngurah Rai Mangrove Forest Bali - Anak Agung Gede Indraningrat; Made Dharmesti Wijaya; Putu Arya Suryanditha; Ayu Savitri Siskayani; Ni Made Defy Janurianti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
In this study we reported cultivation of bacteria associated with mangrove soil from the Ngurah Rai Mangrove Forest, Bali. Mangrove soil samples were serially diluted using sterile artificial seawater, spread onto Starch Casein M agar and incubated at 28oC for 28 days. Cultivation of mangrove soil samples yielded 165 bacterial colonies with 68 isolates were selected and purified based on different morphology. Of these 68 isolates, 22 isolates displayed antibacterial activities ranging from weak to strong inhibition against at least one of four bacterial indicators namely Staphyloccocus aureus, Streptococus mutans, Escherichia coli and Klebsiella pneumoniae using perpendicular streak method. Overall, 19 out of 22 bacteria isolates displayed weak antibacterial potential and two isolates exhibited moderate antibacterial activity. The isolate SA4 was the only bacterium with strong antibacterial potential with measured clear distance ≥ 10 mm against the four bacterial isolates. Sequence analysis based on 16S rRNA gene fragment assigned the isolate SA4 as Bacillus subtilis strain BIL/BS-168. Overall, this study confirmed the untapped potential of antibacterial activities from bacteria associated with mangrove soil.